Determinants of Capital Structure: An Empirical Investigation from UK listed firm panel data - Vassiliades, Constantinos (2014)
This study explores the factors determining the capital structure of UK listed companies and their impact on different debt levels. In order to investigate the factors influencing the capital structure decisions, a panel data set of 191 non-financial firms across 9 different industries on FTSE350 from 2004-2013 was analysed. Total leverage, long-term leverage and short-term leverage served as the dependent variables and were all computed based on their book value. The explanatory variables such as non-debt tax shields, profitability, size, tangibility, growth, liquidity and industry classification were chosen in accordance to the literature and they were thoroughly investigated. Industry classification was examined by one-way analysis of variance (ANOVA), while for the rest of the determinants the Fixed Effect regression model was used.